Romania : Request for Stand-By Arrangement; Staff Report; Staff Supplements; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
Romania's GDP growth averaged more than 6 1\2 percent per year from 2003 to 2008, as foreign direct investment and capital inflows helped finance high consumption and investment growth. The staff report for Romania's request for a Stand-By Arrangement is also elaborated. Robust export growth to EU countries reflected the process of increasing economic integration with western European economies. The rapid increase in borrowing that fueled the boom left Romania highly exposed to global financial difficulties and to exchange rate volatility.